Pengaruh Model Belajar Aktif Tipe Giving Question and Getting Answer (GQGA) Terhadap Prestasi Belajar Bahasa Inggris - Diyansyah, Harno (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The purpose of this study was to determine whether the active learning model of the Giving Question and Getting Answer (GQGA) type affects the English learning achievement of students who use the expository learning method and whether there is a relationship between the active learning model of the Giving Question and Getting Answer (GQGA) type and students' English learning achievement. All students of grade X of SMK NU Singajaya, totaling 320 students, divided into 8 classes, were the subjects of this study. Two experimental classes were randomly selected; the experimental class used the Giving Question and Getting Answer active learning model, and the control class used the expository learning method. The final test, the English learning achievement test, was given after different treatments were given to the two classes. In response to the test results, descriptive analysis was conducted to determine the mean, variance, and standard deviation of the two sample classes. After that, hypothesis testing was conducted, including the Chi-Square test for normality, the F test for homogeneity, and the t test to determine the research hypothesis. The results of the data analysis that had been carried out obtained an average of the experimental class of 74.16 and an average of the control class of 61.54. The hypothesis test used was the t-test and obtained a value of 86.6 t count and 38.2 t table. Because t table and t count , then reject HO and accept Ha. In other words, the English learning achievement of students who use the active learning model type Giving Question and Getting Answer is different from students who use the expository learning method. This is the result of two different approaches. Students who use the active learning model type Giving Question and Getting Answer show better achievement compared to students who use the expository learning method. Therefore, it can be concluded that students' English learning achievement is influenced by the active learning model type Question and Answer. According to this study, English teachers must be able to use the active learning model type Giving Question and Getting Answer (GQGA) as an alternative English learning model. This will help create an active, comfortable, and conducive classroom environment. Therefore, it can be concluded that students' English learning achievement is influenced by the active learning model type Question and Answer. According to this study, English teachers must be able to use the active learning model type Giving Question and Getting Answer (GQGA) as an alternative English learning model. This will help create an active, comfortable, and conducive classroom environment.